Quality-Cost Analysis of Gasoline Production Process (Journal of Engineering, 2013)
Process capability provides a quantitative measure for gasoline production conformance to specifications.It was measured throughout four consecutive months of the last quarter of 2011. Results revealed high percentages (up to 44%) of non conforming gasoline blends to Iraqi marketing specifications for petroleum products (2000) by inspecting 122 different samples of Iraqi regular gasoline (RON 85).Quality cost analysis as an important financial control tool was carried out to evaluate Cost of Quality (COQ) which was large due to non conforming gasoline reached up to (722.8 M.ID) in October. In this research COQ was investigated in order to identify the opportunities of gasoline quality improvements through production process. Also customers’ direct cost loss due to poor gasoline quality was verified and calculated, where amounted to its highest value (9.084960 M.ID) at November.